The fiscal incentive of GHG cap and trade. Permits may be too cheap and developed countries may abate too little - Jørgen Juel Andersen; Mads Greaker (Statistics Norway, Research Department, 2014)
The theoretical justification for a greenhouse gas (GHG) cap and trade system is that participants will trade emission permits until their marginal costs of abatement equal the equilibrium price of emission permits. Abatement is then globally cost efficient. We demonstrate, however, that when the "participants" are national governments this logic may no longer apply: when a national government struggles to raise its desired first-best amount of funds for the provision of public goods, the option of emission trading generates a fiscal incentive that is, generally, inconsistent with a cost effective distribution of abatement. In market equilibrium, global cost efficiency will fail even if just a (small) subset of the participating governments are fiscally constrained: since the fiscally constrained governments will engage in too much abatement, the equilibrium price of GHG emissions will be too low, fiscally unconstrained countries will abate too little, and global GHG abatement costs will not be minimized. Finally, we argue that any institutional change which breaks the direct connection between a national government's abatement policy and its budget is likely to increase welfare.
Keywords: Q55; Q58; 330; climate policy; cap and trade; public goods provision